2015
DOI: 10.1242/jcs.158998
|View full text |Cite
|
Sign up to set email alerts
|

SEPT12 orchestrates the formation of mammalian sperm annulus by organizing SEPT12-7-6-2/-4 core complexes

Abstract: BSTRACTMale infertility has become a worldwide health problem, but the etiologies of most cases are still unknown. SEPT12, a GTP-binding protein, is involved in male fertility. Two SEPT12 mutations (SEPT12 T89M and SEPT12 D197N ) have been identified in infertile men who have a defective sperm annulus with a bent tail. The function of SEPT12 in the sperm annulus is still unclear. Here, we found that SEPT12 formed a filamentous structure with SEPT7, SEPT 6, SEPT2 and SEPT4 at the sperm annulus. The SEPT12-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 26 publications
2
67
0
8
Order By: Relevance
“…In addition, knock-in mice with the SEPT12D197N mutation, which were used to mimic infertile men with SEPT12D197N, exhibited a high percentage of disorganized sperm annuli and necks [27]. To determine whether SEPT12 also affects NDC1 in vivo, IFA was performed in the sperm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, knock-in mice with the SEPT12D197N mutation, which were used to mimic infertile men with SEPT12D197N, exhibited a high percentage of disorganized sperm annuli and necks [27]. To determine whether SEPT12 also affects NDC1 in vivo, IFA was performed in the sperm.…”
Section: Resultsmentioning
confidence: 99%
“…In humans, the mutated SEPT12D197N (Asp197Asn), SEPT12T89M (Thr89Met), and SEPT12Del (c.474G/A induced truncated form) caused teratozoospermia and oligozoospermia [14,15,16]. To mimic the effect of SEPT12D197N in vivo, we generated knock-in mice [27], for which, as Figure 5 illustrates, the NDC1 patterns were irregular and dispersed around the manchette region of the sperm head and tail. This phenomenon may be attributed to the following: (1) the disrupted SEPT12 affects NDC1 localization or (2) the degradation of mutated SEPT12 affects the sperm formation resulting in the mislocalization of NDC1.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the significant region detected in BTA25 but at 3–4 Mb also contains candidate genes for bull fertility, such as SEPT12 and MGRN1 . Indeed, SEPT12 is expressed specifically in the testis and encodes a GTP-binding protein that has been implicated in sperm morphogenesis, sperm motility and male infertility [52, 53]. Likewise, the gene MGRN1 is widely expressed in the male reproductive system, and recent studies have shown that MGRN1 knockout in mice results in male infertility, with disruption of hormones secretion and impaired sperm motility [54].…”
Section: Discussionmentioning
confidence: 99%
“…In sperm from the SEPT4-null mice, basigin, a membrane protein that moves freely but is usually confined to anterior region of the tail, was found distributed all over the tail's plasma membrane, indicating that the compartmentalizing forces had been lost with the loss of the septin ring (Kwitny et al, 2010). The ring-like distribution is not always the only septin pattern in sperm, as later studies using human sperm showed septins, such as SEPT12, SEPT6 and SEPT2, localized from the centriole to the annulus (Kuo et al, 2015; Figure 2A). …”
Section: Localization Of Septins In Ciliamentioning
confidence: 94%